Effectiveness of interventions to optimise dietary intakes in the first 1000 d of life in Indigenous children: a systematic review. Issue 2 (15th February 2022) - Onifade, Oyepeju; Kocanda, Lucy; Schumacher, Tracy; Rollo, Megan; Rae, Kym; Pringle, Kirsty G
Abstract: Objective: Indigenous infants are disproportionately more likely to have negative outcomes compared to non-Indigenous infants with suboptimal nutrition in the first 1000 d playing a major role. This review aimed to systematically assess the effectiveness of interventions designed to optimise dietary intake and/or nutrition-related behaviours among Indigenous infants globally and to identify whether Indigenous populations were involved in the co-design of the intervention. Design: Articles published before June 2020 that reported nutrition-related interventions and outcomes for Indigenous infants were identified from a database search. Data extracted included study aims and design, target population, geographical location, the health condition of the participants, intervention characteristics and outcomes. A narrative synthesis consisting of effects and acceptability of the interventions and involvement of participants in the study design were highlighted. Settings: Population-based intervention studies that focused on improving dietary intakes and/or nutrition-related behaviours of Indigenous infants in the first 1000 d of life were included in this review. Results: Of the 2784 studies identified, three studies met the inclusion criteria. These were conducted among two Indigenous tribes in Guatemala and the USA. Two studies reported the food and nutrient intake of participants with one study showing an improvement in dietary intake of the infants. Only one study reported community participation in the study design, intervention design and implementation, and acceptability of the intervention by the participants. Conclusion: Engaging Indigenous communities throughout the entire process of nutrition interventions could have beneficial effects through improved outcomes in the first 1000 d of life.